Electroencephalographic findings in ATRX syndrome: A new case series and review of literature. (September 2022) - Aiello, Salvatore; Mancardi, Maria Margherita; Romano, Alfonso; Santucci, Margherita; Scaduto, Maria Cristina; Vari, Maria Stella; Striano, Pasquale; Operto, Francesca Felicia; Elia, Maurizio; Vitiello, Giuseppina; Del Giudice, Ennio; Terrone, Gaetano
Abstract: Alpha-thalassemia X-linked intellectual disability syndrome (ATRX) is a rare genetic condition caused by mutations in the ATRX gene characterized by distinctive dysmorphic features, alpha thalassemia, mild-to-profound intellectual disability, and epilepsy, reported in nearly 30% of the patients. To date, different types of seizures are reported in patients with ATRX syndrome including either clonic, tonic, myoclonic seizures or myoclonic absences. However, an accurate analysis of electroencephalographic features is lacking in literature. We report on the epileptic and electroencephalographic phenotype of seven unpublished patients with ATRX syndrome, highlighting the presence of a peculiar EEG pattern characterized by diffuse background slowing with superimposed low voltage fast activity. Likewise, we also review the available literature on this topic. Highlights: Epilepsy occurs in about 30% of patients with ATRX syndrome. Generalized seizures including clonic, tonic, myoclonic or myoclonic absences are frequently described in this syndrome. We report on seven unpublished Italian patients with ATRX syndrome, focusing on epilepsy and EEG pattern. We described a typical EEG pattern characterized by diffuse background slowing with superimposed low voltage fast activity.